ANALISIS MIKROSTRUKTUR NANOPARTIKEL CeO2 DIDOPING Zn YANG DISINTESIS MENGGUNAKAN METODE PRESIPITASI - Ririn Futikhaningtyas; Nurul Wahyu Puspaningrum; Iis Nurhasanah (Youngster Physics Journal, 2013)
Zn-doped CeO2 nanoparticles with various Zn content of 0 - 20% have been synthesized by using precipitation method in the solvent mixture of aquades and isopropanol at room temperature.  The precipitant was calcinated at temperatur 300oC for 3 hours.  The structural properties of CeO2 nanoparticles were characterized by using x-ray diffraction.  X-ray diffraction pattern was analyzed to investigate the influence of Zn doping on crystalite size, lattice constant and lattice strain of CeO2 nanoparticle.  Observation to the peaks diffraction indicate that all of the CeO2 nanoparticle with various Zn doping have cubic fluorite structure and lattice constants in the range 5,4155 Å – 5,4254 Å.  The crystallite sizes of 6 – 11 nm were obtained by Williamson-Hall plot method.  Incorporation of Zn to the CeO2 nanoparticle decrease the crystallite size.  The crystallite size of Zn-doped CeO2 nanoparticles is depend on Zn%. Keywords: CeO2, nanoparticle, precipitation, lattice constant, x-ray diffraction